Optimizing Recovery Through Early Mobilization After Herniorrhaphy: A Case Report - Aldira, Nadya; Pitora, Tobi; Puspita Ningrum, Tita; Okatiranti (Department of Nursing, Faculty of Medicine, Universitas Tanjungpura, 2026)
Hernia remains a disease with increasing incidence worldwide and is commonly treated with surgical procedures. In the postoperative period, wound pain is common, leading to immobilization and the risk of pain; therefore, early mobilization is necessary to prevent this. The purpose of this scientific study was to determine the application of early mobilization in pain management in patients after herniorrhaphy surgery. This study used a case report method with a patient, a 72-year-old man diagnosed with a left scrotal hernia. The patient complained of postoperative wound pain and felt unable to move 6 hours after the procedure. The authors determined the primary diagnosis as decreased physical mobility related to pain. Implementation was carried out using an evidence-based practice approach, with early mobilization delivered according to established standards. The results showed that early mobilization effectively reduced pain intensity from an initial score of 6 to 3. Furthermore, there was a gradual increase in the patient's ability to sit, stand, and walk with assistance for at least 24 hours. Analysis showed that the patient's mobility capacity increased significantly after the implementation of early mobilization.